Cluster expansion for the description of condensed state: crystalline cell approach - Bokun, G.S.; Holovko, M.F. (Condensed Matter Physics, 2018)
A well-known cluster expansion, which leads to virial expansion for the free energy of low density systems, is
modified in such a way that it becomes applicable to the description of condensed state of matter. To this end,
the averaging of individual clusters over the states of an ideal gas is replaced by the averaging over the states
of a non-correlated crystal using single-particle cell potentials. As a result, we arrive at the expansion of the
partition function in correlations on the basis of single-particle functions corresponding to the multiplicative
approximation. The cell potentials defining these functions are found from the condition of the minimum of the
remainder in the constructed decomposition. Широко вiдоме групове розвинення, яке приводить до вiрiального розвинення для вiльної енергiї розрiджених систем, модифiковано так, щоб його можна було застосовувати до конденсованого стану речовини. Для цього усереднення окремих кластерiв по станах iдеального газу замiнюється усередненням по
станах некорельованого кристала, використовуючи комiрковi одночастинковi потенцiали. В результатi
отримано розвинення статистичної суми по кореляцiях на базисi одночастинкових функцiй, якi вiдповiдають мультиплiкативному наближенню. Ґратковi потенцiали, що визначають вказанi функцiї, знаходяться
з умови мiнiмiзацiї залишку в сконструйованому розвиненнi.